Pancreatic Insufficiency Secondary to Tobacco Exposure: A Controlled Cross-Sectional Evaluation. Issue 2 (February 2017) - Raphael, Kara L.; Chawla, Saurabh; Kim, Sungjin; Keith, Christopher G.; Propp, David R.; Chen, Zhengjia N.; Woods, Kevin E.; Keilin, Steven A.; Cai, Qiang; Willingham, Field F.
Abstract : Objectives: Tobacco exposure is an established risk factor for pancreatic cancer and chronic pancreatitis; however, its role in pancreatic insufficiency is not clear. Methods: This controlled, cross-sectional study examined smokers and nonsmokers with no history of pancreatic disease. Histories and validated inventories of alcohol and tobacco use were obtained, and pancreatic insufficiency was assessed using the fecal elastase-1 assay. Results: Of 7854 patients approached, 226 were interviewed and 200 enrolled. The rates of pancreatic insufficiency [18% (18/100)] and severe pancreatic insufficiency [10% (10/100)] were significantly higher in smokers than in controls [6% (6/100), P = 0.009 and 1% (1/100), P = 0.010, respectively]. On multivariate logistic regression, the risk of pancreatic insufficiency in smokers was significantly increased [odds ratio, 4.34 (1.37–13.75); P = 0.012], controlling for alcohol use and relevant covariates. Tobacco exposure was associated with the highest odds ratio for pancreatic insufficiency. Alcohol consumption was strongly associated with tobacco exposure ( P < 0.001), but not with pancreatic insufficiency by multivariate analysis ( P = 0.792). Conclusions: This study suggests that tobacco exposure is independently associated with pancreatic exocrine insufficiency in patients without a prior diagnosis of pancreatic disease. Tobacco exposure seems to have greater detrimental effects on pancreatic function than alcohol in this population.